2017
DOI: 10.1111/jph.12575
|View full text |Cite
|
Sign up to set email alerts
|

Host range, mating type and population structure of Magnaporthe sp. of a single barley field in São Paulo state, Brazil

Abstract: Brazil is blast disease hot spot because severe epidemics have occurred among wheat, triticale, rye, barley and oat crops. Although the first outbreak of barley blast appeared in 1998, little information is available. Therefore, this study aimed to examine host range, mating type composition and population structure of Magnaporthe sp. from a single barley field in São Paulo, Brazil. To examine pathogenicity, 25 Magnaporthe isolates were inoculated on five, three, two and two cultivars of barley, wheat, oat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…The median (not the mean) of the coefficient of variation estimates were used to evaluate the accuracy of the dissimilarity values [ 60 ]. All these procedures were performed in RStudio software [ 61 ] as in Urashima et al (2017) [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…The median (not the mean) of the coefficient of variation estimates were used to evaluate the accuracy of the dissimilarity values [ 60 ]. All these procedures were performed in RStudio software [ 61 ] as in Urashima et al (2017) [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with M. oryzae pathotype Oryza, sexual reproduction is more frequent in MoT, as reflected in its high diversity found in fields (Urashima et al, 1999). However, the predominance of only one mating type suggests asexual reproduction as the predominant mode of reproduction (Urashima et al, 2017). Maciel et al (2014) reported a mixed reproductive system occurring for MoT where a best-fit strain produced by sexual reproduction is maintained generation after generation by asexual reproduction.…”
Section: Understanding the Enemy (Pathogen)mentioning
confidence: 98%
“…Fungicides become ineffective under high-disease pressure or congenial environmental conditions against the disease (Kohli et al, 2020). It is reported that sometimes even four sprays were not able to completely control WB infection in some areas of Brazil (Urashima et al, 2017), thereby affirming the fact that genetic resistance in combination with fungicides is much needed (Ceresini et al, 2018). Although fungicides are mostly used at the heading stage, their application at the seedling stage is also important in reducing inoculum load on basal or older leaves .…”
Section: Fungicides For Wheat Blast Managementmentioning
confidence: 99%
“…, ) to produce strains that are aggressive pathogens of both rice and wheat. Although there are currently no P. oryzae lineages adapted to barley or oats, these could evolve if epidemics become common in these crops (Urashima et al ., ). The potential for the evolution of new threats from P. oryzae should not be underestimated.…”
mentioning
confidence: 97%